The Process of Transforming Farmers into Entrepreneurs in Indonesia - Heri Cahyo Bagus Setiawan; Beni Dwi Komara; Aries Kurniawan (STEI Kanjeng Sepuh Gresik Jawa Timur, 2023)
This study will only examine two things, namely: (1) how is the process of transforming farmers into entrepreneurs and (2) what benefits are obtained by participants who work as farmers while participating in the agripreneur academy program from the Sang Matahari Educational Institute (LPSM). The approach in this study uses an exploratory qualitative approach. From the results of the research and discussion that we analyzed, it was concluded that the transformation process from farmer to entrepreneur who took part in the agripreneur academy education program at LPSM in Sidoarjo, was as follows: (1) Curriculum designed to educate participants to become entrepreneurs in agriculture and plantations; (2) The entrepreneurial mindset of farmers as participants in the agripreneur academy is that farmers aspire to be entrepreneurs and have the motivation to develop their farming/agriculture business through networking and enriching the vision and mission; (3) The process of transforming from a farmer into an entrepreneur is known from two major changes, namely the transformation of farmers from cultivation to market-oriented farmers and from traditional farmers to managerial entrepreneurs.